Trapa natans husk-derived carbon as a sustainable electrode material for plant microbial fuel cells. (1st November 2022) - Lin, Fang-Yi; Lin, Yao-Yu; Li, Hsin-Tien; Ni, Chung-Sheng; Liu, Chao-I; Guan, Chung-Yu; Chang, Chao-Chin; Yu, Chang-Ping; Chen, Wei-Shan; Liu, Tzu-Yin; Chen, Han-Yi
Highlight: Trapa natans husk-derived carbon is a sustainable electrode material for PMFCs. The power density is 55 mW m −2, which is higher than pure graphite felt electrode. High surface area and O-containing groups of TNH-GBG enhance the power density. TNH-based PMFC-SC exhibits high potential for low-cost power generation system. Abstract: The plant microbial fuel cell (PMFC) is a novel technology that can be used to convert solar energy into electrical energy using microbes in the rhizosphere of plants. However, low power density is one of the major obstacles to the development of PMFCs. In this study, we show that the Trapa natans husk-derived carbon (TNH-GBG) is a potential sustainable electrode material for the Canna indica -based PMFCs. The results of the polarization curve measurements showed that the maximum power density of the PMFC utilizing the TNH-GBG-coated graphite felt as the electrodes could reach 55 mW m −2 . This was considerably higher than that of the PMFC with pure graphite felt electrodes (22 mW m −2 ). The enhanced power density of the TNH-GBG was attributed to its high surface area and high content of oxygen-containing groups on the surface of carbon, which enhanced the hydrophilicity and possibly enhanced the microbial attachment, thereby reducing the activation polarization. Furthermore, when the PMFC (with TNH-GBG-coated graphite felt electrodes) was connected to an external load (1000 Ω), a power density of 20 mW m −2 was maintained for over 10 days, which is also higher than that of the PMFC with the graphite felt electrodes. The PMFC with the TNH-GBG-coated graphite felt electrodes shows a similar performance with the one with commercial activated carbon-coated graphite felt electrodes. However, the price of the TNH-GBG is only one-fifth of the commercially activated carbon. Furthermore, the TNH-based PMFC-supercapacitor system was assembled, and it demonstrated that TNH is a potential low-cost electrode material for sustainable power generation-energy storage applications.